An Inertial Method for Split Common Fixed Point Problems in Hilbert Spaces - Haixia Zhang; Huanhuan Cui (Journal of Mathematics)
In this paper, we consider the split common fixed point problem in Hilbert spaces. By using the inertial technique, we propose a new algorithm for solving the problem. Under some mild conditions, we establish two weak convergence theorems of the proposed algorithm. Moreover, the stepsize in our algorithm is independent of the norm of the given linear mapping, which can further improve the performance of the algorithm.